PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA APLIKASI MATIFIC TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN MATEMATIKA KELAS V SEKOLAH DASAR NEGERI 33 PONTIANAK BARAT - Rizkawati, Dhiny; Hartoyo, Agung; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2025)
This research aims to analyze the influence of problem-based learning model assisted by the Matific application This study investigated the impact of problem-based learning (PBL) with Matific application support on fifth-grade students' critical thinking in mathematics at State Elementary School 33 West Pontianak. Employing a quasi-experimental design with a nonequivalent control group, the research targeted all fifth-grade students. Samples comprised 26 students from class V A (experimental) and 28 from class V B (control). Data were gathered through essay-based written tests, assessing students' critical thinking. Post-test averages were compared between the experimental and control groups. A Mann-Whitney U Test revealed a significance level of 0.000 (p < 0.05), indicating a statistically significant effect of PBL with Matific on critical thinking. The effect size, calculated at 0.70, signified a moderate impact. These findings support the hypothesis that PBL integrated with Matific positively influences critical thinking abilities in mathematics. In essence, this research demonstrates the effectiveness of technology-enhanced, problem-based learning in developing critical thinking skills among elementary school students.